Kajian Etnosains Dalam Proses Pembuatan Tempe Gembus Dalam Pembelajaran IPA - Ananda, Mia Lisy; Widodo, Wahono; Istiq’faroh, Nurul (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2025)
Local wisdom in society is rich in indigenous scientific knowledge. However, the reconstruction of original science in society into scientific science is still very limited. This research is based on the limited reconstruction of original science that developed in society into scientific science that can be used by students as an independent learning resource. Research on "Ethnoscientific Studies in the Process of Making Gembus Tempe in Science Learning" is crucial to carry out, considering that no one has yet done a comprehensive analysis of this topic. It is important to carry out this research so that the truth of the research potential can be known and can be used as a consideration in preparing further learning designs. The aim of this research is to reconstruct the original science of the community regarding the process of making tempe gembus into scientific science, as well as explaining the science material related to the reconstruction of original science in the process of making tempe gembus. This research uses a qualitative descriptive method. The data in this research was obtained from interviews, observations, documentation, and literature review to find out the process of making tempe gembus. The research data obtained was then analyzed in several stages, namely data reduction, data display, and drawing conclusions or verification. The results of the research show that the process of making tempeh gembus carried out by the community can be interpreted into scientific knowledge and implemented in science learning.